Reproduction of real-world road profiles on a four-poster rig for indoor vehicle chassis and suspension durability testing. (August 2017) - Chindamo, Daniel; Gadola, Marco; Marchesin, Felipe P
Indoor testing should reproduce the real-world environment in order to be effective. In this article, an efficient methodology to reproduce road profiles on a four-poster rig is presented: such a method includes a complex rig control strategy based on an iterative process. Road profiles come from a purposely designed set of sensors fitted on the car which remains the same regardless of the vehicle or surface type. Particular stresses such as speed humps, potholes and manholes can be reproduced as well. Since there are no previous similar studies, a validation is provided by comparing road and rig data streams and using the maximum absolute error and root mean square error as performance indexes. Results show that the rig is able to reproduce road profiles and the related inputs to the vehicle successfully; hence, the method is reliable and effective.